KAJIAN PRODUKSI DAN KESESUAIAN FISIK KIMIA PERAIRAN UNTUK BUDIDAYA Gracilaria sp DI KABUPATEN MOROWALI - Nasmia, Nasmia; Raihani Ya’la, Zakirah (AgriSains, 2012)
This study aimed to estimate the production of seaweed and assessed the physical and chemical suitability of waters for Gracilaria sp. Farmin in Morowali. Location of data sampling consisted of two observation stations covering District Petasia (Station 1) with 6 substation samplings. Each substation consisted of 3 sampling points. Witaponda district (Station 2) consistied of 6 substations. Sampling was done in each substation with 3 point sampling. The study was conducted for 2 years from April 2011 to December 2012, with collecting primary and secondary data. Target achievement of this research used a survey method with direct field sampling with simple random sampling, purposive sampling and GIS method for compatability. Production of Gracilaria sp in 2011 was as much as 1.39 tonnes/ha/year, in 2012 was 1.8 tonnes/ha/year. On the cultivation of Gracilaria sp at Station 1, suitable (S1) area of 71.46 ha, less suitable (S2) covering an area of 176.6 ha, not suitable (S3) class covering an area of 1.8 ha, while in the corresponding at station 2, (S1) covering 586 , 8 ha, less appropriate class (S2) covering an area of 1740.4 ha.